Pendekatan Gaussian Peluang Galat Bit Asup-Jamak Berbagi-Sandi Multi-Kanal dengan Tunda Sinkron - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2008)
In common Code-Division Multiple-Access (CDMA) systems, a transmitter conveys several orthogonally-coded channels. A transmitter is distinguished to the others using a unique pseudonoise (PN) scrambling code. Multiple-access interference (MAl) occurs because those scrambling codes are not orthogonal each others. This research attempts to formulate the analytical estimation of bit-error probability (BEP), based on Gaussian approximation (GA). The media is assumed doesn't exhibit multipath phenomena, and the delay time of each transmitted signals are in multiple integer of chip duration. For verifying the resulted formula, a dedicated simulation program has been created using Borland Delphi. This simulation program accommodates up to eight transmitters with no more than 64 channels per transmitter. The result informs that GA can yet be used in multi-orthogonally-coded-channel case, by excluding those orthogonal channels in calculating the MAl power. The analytic estimation using GA, of course, is too optimistic for small number of transmitters. As numerical descriptions, with one interferer, the GA BEP estimation is about 37 % lower than its corresponding simulated BER. This difference drops to only about 2 % for seven interferers.